2022
DOI: 10.1108/ebhrm-04-2021-0064
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive leadership and workers' safety behaviour during Covid-19 pandemic

Abstract: PurposeCOVID-19 pandemic underlines the need for effective leadership to resolve the crisis. This study aims to examine the impact of inclusive leadership on safety behaviours via the mediating role of the safety climate.Design/methodology/approachThis research studied and compared two of the industries most affected by the pandemic, specifically banking and education. The questionnaire was undertaken among 111 from the education sector and 159 from the banking sector. Structural equation modelling – partial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
2
0
1
Order By: Relevance
“…Even in the WFH context, previous studies have demonstrated that IL has a positive impact on work engagement, and can therefore be implemented by an organisation to help it perform better during a WFH period (Gill and Berliyanti, 2022). Furthermore, IL has also been shown to have a positive effect on employees' behavioural intention, and especially on employees' safety behaviour during the COVID-19 pandemic (Kusumawardani et al ., 2022). Krause (2020) has indicated that IL promotes a good work-life balance, which is one of the main factors that determines the success of WFH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even in the WFH context, previous studies have demonstrated that IL has a positive impact on work engagement, and can therefore be implemented by an organisation to help it perform better during a WFH period (Gill and Berliyanti, 2022). Furthermore, IL has also been shown to have a positive effect on employees' behavioural intention, and especially on employees' safety behaviour during the COVID-19 pandemic (Kusumawardani et al ., 2022). Krause (2020) has indicated that IL promotes a good work-life balance, which is one of the main factors that determines the success of WFH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study by Kusumawardani et al (2022) about inclusive leadership and workers' safety behavior during the Covid-19 pandemic in Indonesia, it was found that inclusive leadership improves safety behavior among employees through the fostering of a safety climate. In another study by Hudie, Yun and Fuqiang (2017) about inclusive leadership, POS and work engagement, it was revealed that the influence of inclusive leadership on work engagement is mediated by POS.…”
Section: Background Of the Studymentioning
confidence: 99%
“…En este contexto, el bienestar laboral surge como una estrategia empresarial que, lejos de ser novedosa, adquiere elevado interés por cuanto ejerce una relación simbiótica entre las personas trabajadoras y la empresa. Así, cuando las personas trabajadoras encuentran que las condiciones psicosociales en la empresa le son favorables, aumentan su compromiso y su desempeño (Castro-González & Bande, 2019;Guest, 2017;Kusumawardani et al, 2022;Lundqvist et al, 2023;Santiago-Torner, 2023;Vila-Vázquez et al, 2018).…”
Section: Introductionunclassified